+0  
 
0
211
1
avatar+3027 

Help.

NotSoSmart  Nov 16, 2017
 #1
avatar+88898 
+1

y = -x^2 + 12x - 4

 

We need to complete the square, NSS

 

Factor out the negative

 

y = - ( x^2 - 12x + 4)

 

Take 1/2 of -12  = -6   square it  = 36....add it and subtract it inside the parentheses

 

y = - (x^2 - 12x + 36 + 4 - 36)     factor the first three terms, simplify the rest

 

y = - [  ( x - 6)^2  - 32 ]      apply the negative back across the terms

 

y =  - (x - 6)^2  + 32

 

In the form, y = a (x - h)^2 + k   the vertex is (h, k)  =  ( 6 , 32 )

 

 

cool cool cool

CPhill  Nov 16, 2017

16 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.